AL-MASHLAHAH AL-MURSALAH AND ISTISHLAH IN SHARIA ECONOMIC PRACTICE - Zakiah, Zakiah; Amsari, Syahrul (Proceeding International Seminar of Islamic Studies, 2023)
Maslahah al Mursalah and Istishlah are two important concepts in Islamic law that are often used in sharia economic practices. Maslahah al mursalah refers to the general benefit which is recognized by the scholars but there is no specific syar'i argument that shows this. Istishlah, on the other hand, refers to the fundamental public interest that cannot be accommodated by existing law or there is no syar'i argument that shows how to handle the situation. In Islamic economic practice, maslahah al mursalah and istishlah are used to determine the right legal solution in situations that are not regulated by Islamic law. For example, in the practice of Islamic finance, maslahah al mursalah can be used to determine investment policies that are profitable for society in general. Istishlah, on the other hand, can be used to determine policies that protect the public interest in situations that are not regulated by existing law. However, the use of maslahah al mursalah and istishlah in sharia economic practices must be carried out with caution and must not conflict with basic Islamic values. In addition, the use of these two concepts must be based on a correct and comprehensive understanding of Islamic law. Overall, maslahah al mursalah and istishlah are important concepts in Islamic law that can be used in sharia economic practices to determine appropriate policies in situations that are not regulated by existing law. However, the use of these two concepts must be done with caution and must not conflict with basic Islamic values.